Absence of stable intermediates on the folding pathway of barnase - Takei, Jiro (The National Academy of Sciences, 2000)
Barnase is one of the few protein models that has been studied extensively for protein folding. Previous studies led to the conclusion that barnase folds through a very stable submillisecond intermediate (≈3 kcal/mol). The structure of this intermediate was characterized intensively by using a protein engineering approach. This intermediate has now been reexamined with three direct and independent methods. (i) Hydrogen exchange experiments show very small protection factors (≈2) for the putative intermediate, indicating a stability of ≈0.0 kcal/mol. (ii) Denaturant-dependent unfolding of the putative intermediate is noncooperative and indicates a stability less than 0.0 kcal/mol. (iii) The logarithm of the unfolding rate constant of native barnase vs. denaturant concentrations is not linear. Together with the measured rate (“I” to N), this nonlinear behavior accounts for almost all of the protein stability, leaving only about 0.3 kcal/mol that could be attributed to the rapidly formed intermediate. Other observations previously interpreted to support the presence of an intermediate are now known to have alternative explanations. These results cast doubts on the previous conclusions on the nature of the early folding state in barnase and therefore should have important implications in understanding the early folding events of barnase and other proteins in general.